2012
DOI: 10.1007/978-3-642-30950-2_27
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Pedagogical Agents’ Prompting and Feedback in Facilitating Co-adapted Learning with MetaTutor

Abstract: Co-adapted learning involves complex, dynamically unfolding interactions between human and artificial pedagogical agents (PAs) during learning with intelligent systems. In general, these interactions lead to effective learning when (1) learners correctly monitor and regulate their cognitive and metacognitive processes in response to internal (e.g., accurate metacognitive judgments followed by the selection of effective learning strategies) and external (e.g., response to agents' prompting and feedback) conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…We know that in real-world classroom settings, there are many factors that can influence learning, and so it is important to consider multiple factors when conducting (2012) engaged participants in the learning session for two hours, which can be seen to some researchers as too long, and to others as an appropriate learning time. In contrast, the MetaTutor (Azevedo et al, 2012a) learning session lasts for one hour. Shapiro (2008) suggested that many different student characteristics, such as prior knowledge, can affect the way they use hypermedia environments, for example hypermedia assisted learning.…”
Section: Moos and Azevedomentioning
confidence: 99%
See 3 more Smart Citations
“…We know that in real-world classroom settings, there are many factors that can influence learning, and so it is important to consider multiple factors when conducting (2012) engaged participants in the learning session for two hours, which can be seen to some researchers as too long, and to others as an appropriate learning time. In contrast, the MetaTutor (Azevedo et al, 2012a) learning session lasts for one hour. Shapiro (2008) suggested that many different student characteristics, such as prior knowledge, can affect the way they use hypermedia environments, for example hypermedia assisted learning.…”
Section: Moos and Azevedomentioning
confidence: 99%
“…Despite the increasing evidence for the effectiveness of self-regulated learning for students' learning outcomes , research has also revealed that students do not enact these effective self-regulated learning strategies during learning (Azevedo, 2005;Azevedo et al, 2012). Interdisciplinary researchers have been designing and developing computer-based learning environments (CBLEs) (e.g., multimedia, hypermedia, intelligent tutoring systems, multi-agent systems) to foster and promote effective self-regulated learning in students as they learn about various topics, such as biology, physics, and ecology (Aleven et al, 2010;Azevedo & Aleven, 2013;Biswas et al, 2010;Graesser et al, 2007;Jonassen & Land, 2012;D'Mello et al, 2013;Lajoie et al, 2013;Lester et al, 2013;Woolf, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in MetaTutor, a hypermedia environment for learning biology, think-aloud protocols have been used to examine which strategies students use, while analysis of students' navigation through the hypermedia environment helps to identify profiles of self-regulated learners (Azevedo et al 2010). Further studies have examined the role of prompts encouraging students to set and monitor specific learning goals (Azevedo et al 2012). The results of these investigations identified the importance of providing timely prompts as well as offering feedback on students' responses to the prompt.…”
Section: Srl and Intelligent Tutoring Systemsmentioning
confidence: 99%